2021
DOI: 10.1177/03331024211028965
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and classification of headache associated with sexual activity using a composite algorithm: A cohort study

Abstract: Background To differentiate primary headache associated with sexual activity from other devastating secondary causes. Methods In this prospective cohort, we recruited consecutive patients with at least 2 attacks of headache associated with sexual activity from the headache clinics or emergency department of a national medical center from 2005 to 2020. Detailed interview, neurological examination, and serial thorough neuroimaging including brain magnetic resonance imaging and magnetic resonance angiography scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Patients often avoid encountering these common daily activities to prevent themselves from the terrifying headaches. These headaches may last for hours long per attack and recur for multiple times within 2–3 weeks of disease onset [ 2 , 15 , 17 , 25 ]. Abrupt blood pressure surges accompanying headache attacks can be seen in more than one-third of patients [ 2 , 14 , 15 ].…”
Section: Clinical Features Significance and Impactmentioning
confidence: 99%
“…Patients often avoid encountering these common daily activities to prevent themselves from the terrifying headaches. These headaches may last for hours long per attack and recur for multiple times within 2–3 weeks of disease onset [ 2 , 15 , 17 , 25 ]. Abrupt blood pressure surges accompanying headache attacks can be seen in more than one-third of patients [ 2 , 14 , 15 ].…”
Section: Clinical Features Significance and Impactmentioning
confidence: 99%
“…As stated for exercise headache, and despite that less than one out of five cases are secondary, explosive sexual headache should be considered as a warning symptom and investigated. The secondary causes of sexual headache include subarachnoid hemorrhage, reversible cerebral vasoconstriction syndrome, cervical or intracranial arterial dissection, hypertensive crisis and hydrocephalus (6,7,(38)(39)(40). In addition to structural (CT/MRI) brain imaging studies, considering the high proportion of vascular lesions in secondary sexual headache, comprehensive vascular imaging of the head and neck is highly recommended.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Studies have shown that subarachnoid hemorrhage precipitated by coitus occurs in 4-12% of all cases with saccular aneurysm and in 4.1% of patients with arterio-venous malformations (11,41). When the patient experiences several episodes of explosive headache during sexual activities, reversible cerebral vasoconstriction syndrome should always be considered (40). Because vasoconstrictions may not be observed at the early stage of this syndrome, follow-up studies may be needed (Figure 3, Table 3).…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…The lifetime prevalence of headache triggered by sexual activity is estimated to be 1-1.6% in two population-based studies (11,12). There is a male preponderance, with male to female ratios of approximately 2:1 to 4:1, and it typically first occurs in their midthirties to mid-forties (10,(13)(14)(15). Intercourse (83-95%) is the most frequently reported sexual act causing headache, followed by masturbation (14-35%) (3,10,16).…”
Section: Epidemiologymentioning
confidence: 99%
“…Primary HSA is predominantly bilateral (61-80%), occipital (58-80%), and with explosive (61-80%) and throbbing (50-90%) sensation (1,10,13,15). The headache lasts several minutes to 24 hours in most patients (13,15), and may be associated with nausea, vomiting, phonophobia, or photophobia, but without autonomic or vegetative symptoms (1,10,13,15). Some patients 1. increasing in intensity with increasing sexual excitement 2. abrupt explosive intensity just before or with orgasm D. Lasting from 1 minute to 24 hours with severe intensity and/or up to 72 hours with mild intensity E. Not better accounted for by another ICHD-3 diagnosis may have comorbidities of hypertension, migraine, or tension-type headache (10,13,15).…”
Section: Clinical Featuresmentioning
confidence: 99%